What We Need to Know About Retirement: Pressing Issues for the Coming Decade - Kène Henkens; Hendrik P. van Dalen; David J. Ekerdt; Douglas A. Hershey; Martin Hyde; Jonas Radl; Hanna van Solinge; Mo Wang; Hannes Zacher (The Gerontologist, 2018)
The current landscape of retirement is changing dramatically as population aging becomes increasingly visible. This review of pressing retirement issues advocates research on (a) changing meanings of retirement, (b) impact of technology, (c) the role of housing in retirement, (d) human resource strategies, (e) adjustment to changing retirement policies, (f) the pension industry, and (g) the role of ethnic diversity in retirement.
Keywords: 330; life course; older workers; pensions; retirement; work